Choriocarcinoma in Cesarean Scar Site: A Case Report - Helena Azimi; Laya Shirinzadeh; Amir Hosein Jafarian; Behroz Davachi; Somayeh Bolandi; Sepideh Hoseini; Tahereh Zavvari; Zohreh Yousefi; Fatemeh Shirzadeh (Mashhad University of Medical Sciences, 2021)
Background & aim: Cesarean scar pregnancy is an ectopic pregnancy implanted in the myometrium at the site of a previous cesarean section scar and is the rarest kind of ectopic pregnancy. The present study present a case of choriocarcinoma (CC) in the cesarean scar. The clinical course, findings, and treatment plan are discussed. Case report: A 41-years old multi-gravid woman with a history of one previous cesarean section and three subsequent abortions was admitted to the hospital. She suffered from an unknown abnormal vaginal bleeding for two months. Β-HCG titer was 1,000 IU/L and the report of sonography showed no gestational sac. Accordingly, the patient was diagnosed with ectopic pregnancy in the cesarean scar site and, therefore, weekly usage of methotrexate was prescribed for her. Since she did not respond to the treatment, she was referred to our department in the Faculty of Medicine. The evaluation showed mass invasion through the entire uterine wall. The uterus preservation was not possible, therefore, total hysterectomy was performed. The pathology report confirmed CC in the cesarean scar. Conclusion: Based on previous studies, as the number of cesarean sections increases, the possibility of complications rises, as well.  Cesarean scars implantation of CC is one of the rare complications of caesarean section. The probability of a gestational trophoblastic disease should be considered in any woman during her pregnancy. Early detection and proper management of the complications can result in a decrease in morbidity and mortality.